A differential Hall effect measurement method with sub-nanometre resolution for active dopant concentration profiling in ultrathin doped Si1−xGex and Si layers - Daubriac, Richard; Scheid, Emmanuel; Rizk, Hiba; Monflier, Richard; Joblot, Sylvain; Beneyton, Rémi; Acosta Alba, Pablo; Kerdilès, Sébastien; Cristiano, Filadelfo (Beilstein Journal of Nanotechnology, 2018)
In this paper, we present an enhanced differential Hall effect measurement method (DHE) for ultrathin Si and SiGe layers for the investigation of dopant activation in the surface region with sub-nanometre resolution. In the case of SiGe, which constitutes the most challenging process, we show the reliability of the SC1 chemical solution (NH4OH/H2O2/H2O) with its slow etch rate, stoichiometry conservation and low roughness generation. The reliability of a complete DHE procedure, with an etching step as small as 0.5 nm, is demonstrated on a dedicated 20 nm thick SiGe test structure fabricated by CVD and uniformly doped in situ during growth. The developed method is finally applied to the investigation of dopant activation achieved by advanced annealing methods (including millisecond and nanosecond laser annealing) in two material systems: 6 nm thick SiGeOI and 11 nm thick SOI. In both cases, DHE is shown to be a uniquely sensitive characterisation technique for a detailed investigation of dopant activation in ultrashallow layers, providing sub-nanometre resolution for both dopant concentration and carrier mobility depth profiles.
Keywords: carrier mobility; contact resistance; differential Hall effect; dopant activation; fully depleted silicon on insulator (FDSOI); laser annealing; sub-nanometre resolution